1991
DOI: 10.1080/07391102.1991.10507939
|View full text |Cite
|
Sign up to set email alerts
|

Amide Isosteres of Lexitropsins: Synthesis, DNA Binding Characteristics and Sequence Selectivity of Thioformyldistamycin

Abstract: The synthesis and properties of an amide isostere of the antibiotic distamycin, thioformyldistamycin 3 is described. Compound 3 exists predominantly in the E conformation of the thioamide group in freshly prepared DMSO solution but is converted into the Z form, predicted by molecular mechanics to be more stable, on standing for 24 h. The coalescence temperature in DMSO is 110 degrees C by 1H-NMR. The thioformyl moiety of 3 is resistant to both peptidase action and acid treatment. Complementary strand MPE footp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

1992
1992
2000
2000

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
2
4
0
Order By: Relevance
“…In common with distamycin and other minor groove binders, the lack of binding of the drugs to GC-containing sequences in DNA can be attributed to steric clashes with the guanine exocyclic 2-amino group projecting into the minor groove of DNA. The footprinting data are fully consistent with previous studies showing that the terminal forrnamido group can be replaced with other entities such as a thioformyl group (Zimmermann et al, 1991;Singh et al, 1992) without markedly affecting the capacity of the ligand to recognize preferentially AT-rich sequences in DNA. Early studies on distamycin analogues showed that an increase in the number of N-methylpyrrolecarboxamide residues generally correlates with an increase in the affinity of the drug for DNA as well as its antiviral activity (Zimmer et al, 1972;Chandra et al, 1972;Kotler & Becker, 1972).…”
Section: Discussionsupporting
confidence: 80%
“…In common with distamycin and other minor groove binders, the lack of binding of the drugs to GC-containing sequences in DNA can be attributed to steric clashes with the guanine exocyclic 2-amino group projecting into the minor groove of DNA. The footprinting data are fully consistent with previous studies showing that the terminal forrnamido group can be replaced with other entities such as a thioformyl group (Zimmermann et al, 1991;Singh et al, 1992) without markedly affecting the capacity of the ligand to recognize preferentially AT-rich sequences in DNA. Early studies on distamycin analogues showed that an increase in the number of N-methylpyrrolecarboxamide residues generally correlates with an increase in the affinity of the drug for DNA as well as its antiviral activity (Zimmer et al, 1972;Chandra et al, 1972;Kotler & Becker, 1972).…”
Section: Discussionsupporting
confidence: 80%
“…Thioformyldistamycin, being a flexible ligand, assumes a slightly twisted conformation to curve along the DNA helix and thereby achieves a snug fit. The conformation of the thioformyl end of the ligand is only slightly different from the energy-minimized conformation of the free ligand itself (Zimmermann et al, 1991). In this arrangement the amide groups of the ligand are in close proximity to several potential hydrogen-bond acceptor sites in the DNA strands.…”
Section: Resultsmentioning
confidence: 89%
“…One key issue concerning the biological potency, however, pertains to the stability of such peptidic ligands toward hydrolytic and/or enzymatic degradation. In order to circumvent this problem, we recently reported the synthesis and peptidase stability of an analog of distamycin A, obtained by replacing the formyl end group by a thioformyl group (Zimmermann et al 1991). This report is an extension of that study and provides detailed information on the DNA binding characteristics of thioformyldistamycin, elucidated from its interaction with a synthetic decadeoxynucleotide d(CGCAATTGCG)2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to gain insight into the interaction of bleomycin with DNA, we have designed and synthesized a series of functional model compounds (36)(37)(38)(39) of bleomycin through conjugation of the simplified metal-chelating subunit AMPHIS (40,41) [methyl [[[2-(2-aminoethyl)amino]methyl]pyridinyl]-6-carboxylhistidinate] with oligo(N-methylpyrrole) lexitropsin (26,(42)(43)(44)(45) residues which are recognized as sequence-selective DNA minor groove binding moieties (46)(47)(48). It has been assumed, but hitherto has not been proven, that metal ions are coordinated at the AMPHIS site and that the oligo(Nmethylpyrrole) moiety of the AMPHIS-lexitropsin hybrid would provide DNA affinity and sequence selectivity, directing the metal binding moiety to sites differing from those of bleomycin.…”
Section: Introductionmentioning
confidence: 99%